The effects of social media live streaming commerce on Vietnamese Generation Z consumers’ purchase intention - Thi Thuy An Ngo; Chi Thanh Bui; Huynh Khanh Long Chau; Nguyen Phuc Nguyen Tran (Innovative Marketing, 2023)
Social media live streaming commerce is an emerging and effective online shopping channel that integrates live streaming and e-commerce through social media platforms. This trend has gained significant attention, particularly from Generation Z, who are drawn to the interactive and entertaining aspects of shopping through live streaming. This study investigates factors affecting the purchase intention of Vietnamese Generation Z consumers in live streaming commerce on social media platforms, assessing the impact of six factors: entertainment, information quality, interactivity, perceived risk, peer customer evaluations and recommendations, and streamers. Using a non-probability sampling, an online survey was conducted among 344 consumers who possess prior experience with social media live streaming commerce. Data analysis used a partial least squares structural equation modeling technique. The findings revealed that increased entertainment, higher information quality, enhanced interactivity, positive peer customer evaluations and recommendations, and a more attractive and expert streamer positively impact purchase intention. Notably, streamers exhibited the most robust influence, while information quality demonstrated the weakest effect among the influencing factors. Conversely, perceived risk did not significantly hinder purchase intention, suggesting Generation Z consumers’ confidence in online transactions and their willingness to take risks for entertainment and interactivity in live streaming commerce. In light of these results, businesses are advised to elevate consumer purchase intentions by prioritizing aspects related to entertainment, information quality, interactivity, and peer customer evaluations. Prudent selection of streamers is highlighted as a pivotal strategy for organizations to effectively shape customer purchasing intentions. AcknowledgmentThe researchers express sincere gratitude to all the participants who generously participated in this study.